Characteristic of Herpes Zoster in the Elderly at Prof. Dr. I.G.N.G. Ngoerah General Hospital: An Epidemiologic Study - Hosea, Felicia Emiliana; Praharsini, I Gusti Ayu Agung (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Herpes zoster is a disease caused by the reactivation of the latent varicella zoster virus. Herpes zoster is the most common infection found in the elderly population. Epidemiologic data on herpes zoster infection among the elderly population in Bali remain limited. Purpose: The purpose of this study is to evaluate the characteristics of herpes zoster infection in elderly patients in order to provide clinical decision-making related to the management and prevention of herpes zoster in the elderly. Methods: This study uses a retrospective descriptive and gets its information from the medical records of herpes zoster patients at the Dermatovenereology Polyclinic at Prof. Dr. I.G.N.G. Ngoerah General Hospital from January 2019 to June 2022. The study population consisted of patients aged 60 years or older who were diagnosed with herpes zoster and received treatment at the polyclinic during the study period. Result: This study found that 33 elderly patients were diagnosed with herpes zoster. The age group 60-69 years found the most herpes zoster, with 18 (54.6%) patients and 17 (51.5%) male patients. The elderly patients had more comorbidities, which are 22 (66.7%) patients, with the majority having cancer, 7 of 22 patients (31.8%). The thoracic dermatome affected 13 patients (39.4%), multidermatome involvement affected 16 patients (48.4%), and post-herpetic neuralgia affected 22 patients (66.7%). Conclusion: This study found that elderly herpes zoster patients were mostly in the age group of 60-69 years, had cancer comorbidities, and involved multidermatomes.